# Complex Number and Quadratic Equations - Solutions and Study Material

### For Video Tutorials on Complex Number and Quadratic Equations Visit Page No - 5

**Complex Number** : Let us denote by the symbol i. Then ,we have = -1. This means that I is a solution of the equation

A number of the form a + ib, where a and b are real numbers, is defined to be a complex .

Complex Number: 2 + 3i, , are complex numbers.

For the Complex Number z = a + ib, a is called the real part, denoted by Re z and b is called the imaginary part denoted by Im z of the *complex number z*. For example, if z = 2 + i5, then Re z = 2 and Im z = 5.

Two complex numbers = a + ib and = c + id are equal if a = c and b = d

**Example:** If 4x + i(3x – y) = 3 + i (– 6), where x and y are real numbers, then find the values of x and y.

**Solution:** We have , 4x + i (3x – y) = 3 + i (–6) ... (1)

Equating the real and the imaginary parts of (1), we get ,4x = 3, 3x – y = – 6,

which, on solving simultaneously, give x = , y =

**Algebra of Complex Numbers: **In this Section, we shall develop the algebra of complex numbers

Addition of two complex numbers Let = a + ib and = c + id be any two complex numbers .Then , the is define as follows :

= (a + c) + i(b + d) , which is again a complex number.

**For Example** (2 + 3i) +(-6 +5i) = (2-6) + I (3 + 5) = (-4 + 8 i)

The addition of complex number satisfy the following properties:

- The closure law The sum of two complex numbers is a complex number, i.e., is a complex number for all complex numbers Let and Let
- The commutative law For any two complex numbers and ,

- The associative law For any three complex numbers ,

- The existence of additive identity There exists the complex number 0 + i 0 (denoted as 0), called the additive identity or the zero complex number, such that, for every complex number z, z + 0 = z
- The existence of additive inverse To every complex number z = a + ib, we have the complex number – a + i(– b) (denoted as – z), called the additive inverse or negative of z. We observe that z + (–z) = 0 (the additive identity)